Strengthening Diabetes Self-Management Skills in People With Diabetes Mellitus in Kapasa Raya Village - Sulfikar, Andi; Rajab, Alfian; Thalib, Abdul; Musyawir, ahmad (Journal of Evidence-Based Community Health, 2024)
Diabetes Militus (DM) or known as diabetes, is currently a disease that is commonly found This study highlights. The  effectiveness of the counseling intervention "Strengthening Diabetes Self Management in Diabetes Mellitus Patients" in increasing the knowledge of abdimas participants about diabetes management. Before the intervention, the majority of participants had less knowledge about their condition, but after the program was completed, there was a significant improvement where only 40% of participants still had less knowledge, while 60% had acquired good knowledge. The transformation that occurred after the intervention, from expressions of confusion to understanding and confidence, demonstrated the importance of a targeted outreach approach in improving abdimas participants' skills in managing their own diabetes